Urgensitas Keluarga Dalam Menanamkan Nilai-Nilai Pendidikan Keagamaan Pada Anak - Asnawan Asnawan (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Development of the child's age phase. While for families who are less able in their religious knowledge, children's education is left to the Koran teacher. The role of the family in this case is nothing but a motivator for children. The role of the family in instilling worship values in children in the family is huge. The role appears in the efforts of parents to always instill the values of worship and at the same time train children to have a high personality in carrying out their worship. The role of the family in instilling moral values in children is also very large. This form of planting is started by parents starting early.Keywords: Family Education, Diversity Values, Children.